2001
DOI: 10.1007/s003300100852
|View full text |Cite
|
Sign up to set email alerts
|

Accessory fissures of the lung: evaluation by high-resolution computed tomography

Abstract: This study was performed to classify and assess the frequency of accessory fissures of the lung by high-resolution CT (HRCT) scans. The HRCT scans of 443 patients were retrospectively reviewed. After exclusion of patients with pulmonary parenchymal distortion, pleural disease or those who had had lobectomy, 186 patients were included in the study. The HRCT scans consisted of 1.5-mm sections obtained at 10-mm intervals and reconstructed with a high-spatial-resolution algorithm. In 59 of 186 patients (32%), a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 8 publications
5
34
3
1
Order By: Relevance
“…Despite many published reports regarding an azygous lobe, a limited number of studies have examined its prevalence, which is reported to be 1% in cadaveric specimens, 0.4% on plain chest X-rays, and 1.2% on high-resolution CT images (8)(9)(10). A PubMed search on the prevalence of an azygous lobe detected using thoracic CT images yielded a limited number of studies (10,11). Thoracic CT images examined in our study yielded a case prevalence higher than that previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…Despite many published reports regarding an azygous lobe, a limited number of studies have examined its prevalence, which is reported to be 1% in cadaveric specimens, 0.4% on plain chest X-rays, and 1.2% on high-resolution CT images (8)(9)(10). A PubMed search on the prevalence of an azygous lobe detected using thoracic CT images yielded a limited number of studies (10,11). Thoracic CT images examined in our study yielded a case prevalence higher than that previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…Pneumonia may spread to adjacent lobes via parenchymal continuation in case of incomplete fissures. Accessory fissures often are not detected on CT scans, because of incompleteness, thick sections and orientation in relation to particular plane [15] ( Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of an azygos lobe has been reported to range from 0.2% to 1.2% (Boyden, 1952;Chiba et al, 1990;Ariyürek et al, 2001;Aziz et al, 2004). Generally, the azygos lobe has been detected by classical radiography and modern clinical imaging methods (Cohen and Dooneief, 1951;Kolbenstvedt et al, 1979;Speckman et al, 1981;Pomeranz and Proto, 1986;Agrawal et al, 1995;Kobayashi et al, 1995;Caceres et al, 1998;Arslan et al, 2000).…”
Section: Introductionmentioning
confidence: 93%